The Relationship Between Teacher Training in Emotional Intelligence and Classroom Behavior Management in Nigeria - Tunde Akinola; A. T. Olaniyan Johnson (Journal of Advanced Research in Education, 2025)
Emotional intelligence (EI) is increasingly recognized as a critical skill for teachers in managing classroom behavior and fostering effective student engagement. This study outlines a strategic roadmap for integrating EI into teacher training programs in Nigeria, addressing systemic gaps, cultural relevance, and sustainability. Key components include policy reforms to mandate EI training, development of localized and adaptable modules, and collaborative partnerships among governments, NGOs, and academic institutions. Barriers such as lack of institutional support, financial constraints, and societal attitudes are also examined. The proposed framework emphasizes the transformative potential of EI in improving classroom dynamics, enhancing teacher effectiveness, and creating inclusive learning environments. This paper aims to provide a foundation for educators and policymakers to implement EI as a core component of teacher education.